233k views
2 votes
What is
(x−8)(2x+3)=(3x−5)(x+4)\\ as a quadratic equation?

1 Answer

5 votes

Answer:

-x^2 - 20x -4 = 0

Explanation:

I assume you meant (x-8)(2x+3) = (3x-5)(x+4).

Perform the two indicated multiplications and then combine like terms:

2x^2 + 3x - 16x - 24 = 3x^2 + 12x - 5x - 20

Combine the x terms on each side:

2x^2 - 13x - 24 = 3x^2 + 7x - 20

Subtract 3x^2 from both sides:

-x^2 - 13x - 24 = 7x - 20

Subtract 7x from both sides:

-x^2 - 20x - 24 = -20

Add 20 to both sides:

-x^2 - 20x -4 = 0 This is the desired quadratic equation.

User Beartums
by
5.8k points